The Effect of Return On Asset and Total Asset Turnover on Stock Return at PT Bank Central Asia Tbk Period 2014 - 2023 - Oktrima, Bulan; Indriani, Vini (Indonesian Financial Review, 2024)
This study aims to determine the Effect of Return on Assets and Total Asset Turnover on Stock Returns at PT Bank Central Asia Tbk for the 2014-2023 Period. The research method used is a quantitative method with descriptive analysis techniques. The data used are secondary data in the form of annual financial reports of PT Bank Central Asia Tbk for the 2014-2023 Period listed on the Indonesia Stock Exchange or available on the company's website. The methods used include the classical assumption test, which consists of normality, multicollinearity, heteroscedasticity, and autocorrelation tests. In addition, Multiple Linear Regression Analysis Techniques, Hypothesis Tests (t-test), Simultaneous Tests (f-test), and Coefficient Determination Tests were also carried out. The data was tested using the Statistical Product Service and Solution (SPSS) application program version 25.0. It can be concluded that the results of the study show that the ROA value has a significant effect on Stock Returns partially with a significance of 0.001. Total Asset Turnover does not have a significant effect on Stock Return partially with a significance value of 0.123. And simultaneously Return on Asset and Total Asset Turnover have a significant effect on Stock Return. The Determination Coefficient is 98.5% with the remaining 1.5% being part of other factors.